عقود الأسواق المالية المستقبلية والآجلة وآثارها الاقتصادية: دراسة من منظور الاقتصاد الإسلامي - العزي، هاني بن عبدالله (جامعة القلم للعلوم الإنسانية والتطبيقية, 2023)
تناول البحث دراسة عقود الأسواق المالية المستقبلية والآجلة، وهي عقود الخيارات المالية وعقود البيع على المكشوف وعقود المستقبليات والعقود الآجلة، وتم الاقتصار على هذه الأنواع لاحتوائها على المحظورات الشرعية أهمها الغرر، وتم استخدام المنهج الاستقرائي الاستنباطي في توضيح هذه العقود وأحكامها الشرعية، وما فيها من غرر كثير، وذكر الآثار الاقتصادية السلبية لها، وتوصل البحث إلى أن عقود الأسواق المالية المستقبلية والآجلة عقود تحتوي على محظورات شرعية أهمها الغرر، والتعامل بها محرم شرعاً وله آثار اقتصادية سلبية على السوق المالية والاقتصاد، ومن أهم الآثار الاقتصادية زعزعة الاستقرار الاقتصادي، وتحقق الخسارة الاقتصادية لأحد أطراف التعامل بهذه العقود، والتأثير على المستوى العام للأسعار في السوق المالية، وترك الاستثمار في المشاريع الحقيقية والاتجاه نحو المضاربات الوهمية لتحقيق الربح السريع، وترك الاستثمار في المشاريع الحقيقية يؤدي إلى تفشي البطالة في المجتمع، وتأثر الإنتاج، وعدم قدرة المجتمع على التوظيف الكامل للموارد الاقتصادية المتاحة. This article aims to study the future and forward contracts in financial markets and their effects. These are financial options contracts, uncovered sales contracts, future contracts and forward contracts. The study tackles these types of contracts because they contain prohibited practices such as Gharar, which includes usury, fraud, etc. The study employs the inductive deductive approach to pinpoint these contracts and their Sharia provisions, and several Gharar practices. It concludes that future and forward contracts in financial markets contain prohibited practices such as Gharar, dealing with which is prohibited in Islam due to having negative economic effects. The most important economic effects include destabilizing economy, causing economic losses to one of the partners involved in these contracts. This also affects prices in the financial markets, resulting in deviating investment from real projects to unreal speculative investments whose main aim is to achieve quick profits. Neglecting investment in real projects causes unemployment in the society. It also affects production, reducing the ability of society to fully utilize the available economic resources.
Keywords: الاقتصاد الإسلامي -- الأسواق المالية -- الآثار الاقتصادية -- المخالفات الشرعية